EXPLORING HOW CUSTOMER SATISFACTION MEDIATES THE IMPACT OF SERVICE QUALITY, PRICING, AND PROMOTION ON LOYALTY AMONG PRODUCTIVE-AGE CONSUMERS: A CASE STUDY AT XYZ CLINIC IN BANJARMASIN - Kleofas Sumaler; Dadan Abdul Aziz Mubarok (RADJA PUBLIKA, 2025)
This study aims to examine how service quality, price, and promotion influence customer loyalty, with customer satisfaction acting as a mediating variable at XYZ Beauty Clinic in Banjarmasin. A descriptive quantitative approach was applied, using structured questionnaires distributed to 150 respondents who had received services within the past year. Data were analyzed using Structural Equation Modeling with the Partial Least Squares technique. The results show that service quality significantly influences satisfaction, but does not lead to loyalty through satisfaction. In contrast, price and promotion have direct and significant effects on both satisfaction and loyalty. Customer satisfaction does not statistically mediate the relationship between service quality, price, promotion, and loyalty. These findings indicate that customers in the productive age group at XYZ Clinic are more influenced by economic factors and promotional offers rather than emotional satisfaction in forming brand loyalty. This study contributes to understanding the trend of transactional loyalty and highlights the importance of combining emotional connection with clear value propositions to build sustainable loyalty strategies.